Lagochile emarginata (Gyllenhal): morphology of immature and imago, and biological records (Coleoptera, Scarabaeidae, Rutelinae) - Albertoni,Fabiano F. (2014)
Lagochile emarginata (Gyllenhal): morphology of immature and imago, and biological records (Coleoptera, Scarabaeidae, Rutelinae). The last larval instar and pupa of Lagochile emarginata are described. Pupa of the genus Lagochile Hoffmannsegg, 1817 is described for the first time. Redescription of the imago, clarifications on the morphology of immature Scarabaeoidea and biological notes are presented.